An Interesterified Palm Olein Test Meal Decreases Early‐Phase Postprandial Lipemia Compared to Palm Olein: a Randomized Controlled Trial. Issue 9 (8th August 2014) - Hall, Wendy L.; Fiuza Brito, Marcela; Huang, Junlan; Wood, Lucy V.; Filippou, Androulla; Sanders, Thomas A. B.; Berry, Sarah E. E.
Abstract: Palm oil that has been interesterified to produce a higher proportion of palmitic acid (16:0) in the sn ‐2 position reduces postprandial lipemia in young, normolipidemic men and women, but effects in older subjects with higher fasting triacylglycerol (TAG) concentrations are unknown. We tested the hypothesis that high‐fat meals rich in interesterified palm olein (IPO) decrease lipemia and alter plasma lipoprotein fraction composition compared to native palm olein (NPO) in men aged 40–70 years with fasting TAG concentrations ≥1.2 mmol/L. Postprandial changes in plasma lipids following meals containing 75 g fat (NPO and IPO) were compared using a randomized, double‐blind crossover design ( n = 11). Although there were no significant differences in plasma TAG concentrations between meals over the total 6‐h postprandial measurement period, IPO resulted in a decreased plasma TAG response during the first 4 h of the postprandial period (iAUC 1.65 mmol/L h, 95 % CI 1.01–2.29) compared to NPO (iAUC 2.33 mmol/L h, 95 % CI 1.58–3.07); meal effect P = 0.024. Chylomicron fraction TAG concentrations at 4–6 h were slightly reduced following IPO compared to NPO [NPO−IPO mean difference 0.29 mmol/L (95 % CI −0.01–0.59), P = 0.055]. There were no differences in IDL fraction TAG, cholesterol or apolipoprotein B48 concentrations following IPO compared with NPO. In conclusion, consuming a meal containing palm olein with a higher proportion of 16:0 in the sn ‐2 position decreases postprandial lipemia compared to native palm olein during the early phase of the postprandial period in men with higher than optimal fasting triacylglycerol concentrations.